2016
DOI: 10.18632/oncotarget.10208
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of androgen receptor in triple negative breast cancer: A meta-analysis

Abstract: BackgroundAndrogen receptor (AR) is a promising therapeutic target for breast cancer. However, its prognostic value remains controversial in triple negative breast cancer (TNBC). Here we present a meta-analysis to investigate the correlation between AR expression and TNBC prognosis.ResultsThirteen relevant studies with 2826 TNBC patients were included. AR positive rate was 24.4%. AR+ patients tended to have lower tumor grade (p< 0.001), but more lymph node metastases (p < 0.01). AR positivity was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 31 publications
10
79
4
3
Order By: Relevance
“…For example, one study [15] found that AR expression was positively correlated with increased disease free survival (DFS) in patients with luminal breast cancer, while decreased DFS in TNBC. In contrast, a meta-analysis suggested that AR positivity was associated with prolonged DFS in TNBC, but had no significant impact on overall survival [16]. Another preclinical research detected that tumor proliferation is stimulated by androgens and inhibited by AR antagonists with MDA-MB-453 cell model both in vitro and in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study [15] found that AR expression was positively correlated with increased disease free survival (DFS) in patients with luminal breast cancer, while decreased DFS in TNBC. In contrast, a meta-analysis suggested that AR positivity was associated with prolonged DFS in TNBC, but had no significant impact on overall survival [16]. Another preclinical research detected that tumor proliferation is stimulated by androgens and inhibited by AR antagonists with MDA-MB-453 cell model both in vitro and in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, ARs are more frequently present in breast cancer than ERs or PRs [11]. Presence of ARs in ER negative tumors has been related to better disease free survival [1, 12] but high AR expression has also been related to an increased likelihood of axillary metastasis [13], implying that AR expression triggers increased tumor capacity to metastasize, at least in lymph nodes. It is to note, however, that our current knowledge of AR expression and identification is limited to the nuclear form of the classical wild-type AR, and does not take into consideration any extranuclear action or isoform of the ARs.…”
Section: Introductionmentioning
confidence: 99%
“…He et al showed that AR expression is a favorable prognostic factor of disease-free survival and overall survival in patients with TNBC (p=0.032) 22 . In addition, a recent meta-analysis including 13 studies with 2,826 patients evaluated the prognostic factor value of AR in TNBC and concluded that AR expression was associated with lower risk of disease recurrence 23 . In agreement with previous studies 6,8 , the present research showed that strong AR expression is associated with older age (p<0.05) when AR-positive cases are subdivided into weakly and strongly positive, with a higher mean age in the strongly AR-positive subgroup (70.8 years).…”
Section: Discussionmentioning
confidence: 99%